Shelf Life Evaluation of Instant Pasta in Two Different Packaging. - S Murathathunyaluk; P Jindawanich (My University, 2019)
Abstract The objective of this study is to evaluate shelf life of instant pasta which had been packed in two different packaging, type I is an OPP/MCPP sachet and type II is an OPP/CPP sachet, under accelerated condition (37°C, 85%RH) for 12 weeks. There were 2 index which were used to evaluate the shelf life, one was sensory tests and another one was moisture content in pasta. Assessed by sensory tests, the shelf life of instantly cooked pasta packed in type I and type II sachet, were revealed more than 12 weeks and equal 12 weeks, respectively. Likewise, the shelf life predicted on the basis of moisture sorption isotherm and water permeability of packaging material, were estimated at 119 and 46 days in OPP/MCPP and OPP/CPP sachets, respectively. According to these results, the quality changing of instant pasta measured during storage suggested that OPP/MCPP sachet had better protectively effect than the OPP/CPP sachet.
Keywords: Instant; Food composition and properties